2020
DOI: 10.22271/chemi.2020.v8.i3af.9548
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of combining ability and heterosis by using diallel mating design in Kabuli genotypes of chickpea

Abstract: An experiment consisting of six parents and 15 hybrids (developed by using 6 x 6 half diallel mating design) in kabuli chickpea was laid out in RBD design with three replications to estimate combining ability and heterosis. The ANOVA (Analysis of Variance) for different characters revealed highly significant differences among genotypes for all traits under study.The estimates of SCA variance were found to be higher than the GCA variance for all the characters under consideration, indicating good prospects for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Selection for these traits will produce higher achievements during early generations' selection and will give genotypes with large adaptability. It is very clear that the estimates of SCA variance are higher than GCA variances in most traits and this is in agreement with the findings by Sonali et al (2020). General combining ability estimates for lines and testers are presented in Table 2.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Selection for these traits will produce higher achievements during early generations' selection and will give genotypes with large adaptability. It is very clear that the estimates of SCA variance are higher than GCA variances in most traits and this is in agreement with the findings by Sonali et al (2020). General combining ability estimates for lines and testers are presented in Table 2.…”
Section: Resultssupporting
confidence: 87%
“…He reported that the number of pods per plant was the only trait which showed marked hybrid vigour. Since then several reports have been published reporting hybrid vigour in chickpea (Bhatt and Singh, 1980;Singh and Ramanujam, 1981;Gadekar and Dodiya, 2013;Gaur et al, 2020). Selection of mating design and material under the study is very crucial in any breeding programme.…”
Section: Introductionmentioning
confidence: 99%
“…It is a widely used design for self-pollinated species as the success rate for generating complete crosses is often lower (Signh 2007). It has been used in genetic analysis of traits of various legume crop species such as cowpea (Tchiagam et al 2011, Rodrigues et al2018, Owusu et al 2020, soybean (El- Garhy et al 2015, Kurasch et al 2017, Adewale et al 2023) and chickpea (Verma et al 2020, Gaur et al 2020, Lakhote et al 2020. There is a lack of information on combining ability and genetic analyses of Bambara groundnut for agronomic traits.…”
Section: Discussionmentioning
confidence: 99%